Nurses Perception and Role of Euthanasia: A Literatur Review - Satriani, Ni Luh Adi; Sani, Ari Wina; Wangi, Ni Luh Putu Ayu Puspita; Cahyadi, Herry Suwaja; Abdurrahman, Firman; Dewi, Ketut Hendra Yanti (Babali Publisher, 2024)
Introduction: Euthanasia is the most controversial ethical topic in the world of health. Nurses have an important role in providing holistic care for people with life-limiting conditions. However, they experience internal moral conflict and helplessness when patients ask them to assist in the dying process. This literature review aims to determine what is known about nurses' perceptions and attitudes toward euthanasia.Methods: The literature search was carried out using three databases, namely Google Scholar, PubMed, and Scient Direct. The inclusion criteria for the literature search were articles with publication years 2014-2022 in Indonesian or English and complete articles that could be open access. The keywords used in searching for articles were adjusted to the Medical Subject Heading (MeSH), namely knowledge, nurses' attitudes, euthanasia, and nursing euthanasia.Results: The literature review identified fifteen studies for inclusion in the final analysis. One article was semi-experimental, eight articles used a descriptive design with a cross-sectional approach, two articles used an epidemiological descriptive design, and two articles used descriptive-analytical methods. Nurses exhibit a range of attitudes towards euthanasia, including both positive and negative perspectives. Conclusion: The issue of euthanasia has presented a significant challenge for nurses in achieving their goal of providing holistic care. Their personal, professional, and transpersonal perspectives influence nurses' perceptions and attitudes. Potential implications for nurses relate to education, practice, and research. Nurses must be informed about existing laws and provided in-depth education and professional guidance to help guide action. Further research is needed to explore the impact on carers' emotional well-being, clarify their role, and determine the support they may require when engaging in euthanasia.